Efektivitas e-Modul Berbasis Self Organized Learning Environment (SOLE) Pada Materi Biologi Semester Genap Kelas X SMA - Ali, Sutrisno Nurhadi; Adnan, Adnan; Syamsiah, Syamsiah (BIOEDUSCIENCE, 2025)
Test the effectiveness of electronic modules (e-Modules). The hope of this research is to test the effectiveness of Self Organized Learning Environment (SOLE) based e-Modules. This type of research is research and development which refers to the ADDIE type of development (Analysis, Design, Development, Implementation and Evaluation). The resulting product is an e-Module based on Self Organized Learning Environment (SOLE), which was carried out effectively by 34 students. The instrument used is an essay test. The instruments that have been developed are used for data collection. The resulting data was then analyzed quantitatively. Based on the research results, it shows that the level of effectiveness of SOLE-based e-Modules in terms of student learning outcomes is 0.7, which is in the effective category with a medium level. So the SOLE-based e-Module is effective at a moderate level. The suggestion in this research is that it is recommended for researchers who want to continue this research to conduct influence-based experimental research to find out more about how this e-Module will work if it is tested in several schools.